Do benefits of earlier antiretroviral treatment initiation outweigh harms for individuals at risk for poor adherence? - Braithwaite, R Scott; Roberts, Mark S; Goetz, Matthew Bidwell; Gibert, Cynthia L; Rodriguez-Barradas, Maria C; Nucifora, Kimberly; Justice, Amy C (Clinical infectious diseases : an official publication of the Infectious Diseases Society of America, 2009)
Clinicians may defer antiretroviral treatment for patients with suboptimal adherence. We used a validated computer simulation of HIV disease progression to compare alternative treatment thresholds for patients with suboptimal adherence. Earlier treatment increased life expectancy across a wide adherence range (50%-100% of doses taken). Delaying treatment for patients with suboptimal adherence may not always be appropriate.
Keywords: Adult; Antiviral Agents; Computer Simulation; HIV Infections; Humans; Life Expectancy; Medication Adherence; Middle Aged; Time Factors; Treatment Outcome